The Effect of Online Health Education Using Animated Videos and Booklets on Parents' Knowledge of Motor Development Stimulation in Preschool Children - BudiAstuti, Khusnul; Indarwati, Ferika; Rahmah, Rahmah; Suminar, Istinengtyas Tirta (STIKes YARSI Pontianak, 2026)
Background: Parental stimulation plays an important role in supporting the motor development of preschool children, but many parents still lack understanding of age-appropriate stimulation. Objective: This study aimed to determine the effectiveness of animated videos combined with digital booklets in improving parental knowledge about motor development stimulation in preschool children. Method: A quasi-experimental pretest-posttest control group design was used, involving 120 parents selected through purposive sampling, with 60 parents assigned to the intervention group and 60 parents assigned to the control group. Results: Knowledge was measured using a structured questionnaire and analyzed using paired and independent t-tests (p<0.05). The findings indicate that the use of animated videos combined with booklets has a significant impact on improving parental understanding. Conclusion: This study shows that multimodal educational media can improve understanding more effectively than conventional print media. These findings highlight the importance of educational approaches that are accessible, engaging, and user-friendly for parents, with implications for health education programs in early childhood settings.